2017
DOI: 10.1371/journal.pone.0187077
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-124 is a link between measles virus persistent infection and cell division of human neuroblastoma cells

Abstract: Measles virus (MV) infects a variety of lymphoid and non-lymphoid peripheral organs. However, in rare cases, the virus can persistently infect cells within the central nervous system. Although some of the factors that allow MV to persist are known, the contribution of host cell-encoded microRNAs (miRNA) have not been described. MiRNAs are a class of noncoding RNAs transcribed from genomes of all multicellular organisms and some viruses, which regulate gene expression in a sequence-specific manner. We have stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Inhibition of miR-124 expression reduces chikungunya virus (CHIKV) viral production in human cells independently of the direct binding to the viral RNA, supporting the idea that miR-124 may also play a role in the regulation of cellular targets against alphaviruses. This has already been observed for miR-124 regulation of measles virus (47), JEV (48) or HIV (49) infections. In addition, miR-124 expression is modulated by different viruses including ZIKV (50), EV71 (51), HCMV (52) or influenza H1N1 (53) suggesting a possible implication of the miRNA in the regulation of these infections as well.…”
Section: Discussionsupporting
confidence: 58%
“…Inhibition of miR-124 expression reduces chikungunya virus (CHIKV) viral production in human cells independently of the direct binding to the viral RNA, supporting the idea that miR-124 may also play a role in the regulation of cellular targets against alphaviruses. This has already been observed for miR-124 regulation of measles virus (47), JEV (48) or HIV (49) infections. In addition, miR-124 expression is modulated by different viruses including ZIKV (50), EV71 (51), HCMV (52) or influenza H1N1 (53) suggesting a possible implication of the miRNA in the regulation of these infections as well.…”
Section: Discussionsupporting
confidence: 58%
“…Recently we have demonstrated that in MV persistently infected human neuroblastoma cells, high expression of miR-124 correlates with reduced cell division (Naaman et al, 2017). In this work we showed that expression of miR-124 in MV persistently infected BGU-iPSCs was upregulated compared to noninfected cells implying that either more cells became miR-124 positive cells and/or that MV infection led to upregulation of miR-124 expression.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies from our laboratory have shown that RSV infection of A549 cells modifies miR expression (Bakre et al, 2012(Bakre et al, , 2015(Bakre et al, , 2017) however, information regarding miR expression in RSV-or MeV-infected neuronal SHS cells is inadequate (Naaman et al, 2017;Cakmak Genc et al, 2018;Haralambieva et al, 2018). Neuronal cells are not the primary cell type infected by RSV, but they can be infected and may act as a reservoir of infection.…”
Section: Results Sncrnas and Virus-infected Shs Cellsmentioning
confidence: 97%
“…Other studies have shown that the pattern of miR expression is modified following RSV infection of nasal epithelial cells (Inchley et al, 2015;Hasegawa et al, 2018), and PBMCs from children (Wang et al, 2017). Deregulated miR expression occurs in MeV-infected human neuroblastoma cells and PBMCs (Inchley et al, 2015;Yis et al, 2015;Naaman et al, 2017;Hasegawa et al, 2018), as well as in PBMCs from RSV-infected children (Wang et al, 2017). It is known that MeV persistence in neuroblastoma cells is assisted by the downregulation of CDK6, a component of cell cycle progression regulated by miRNA-124 (Riddell et al, 2007;Naaman et al, 2017;Griffin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%